2015
DOI: 10.3389/fped.2015.00003
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Assessment after Surgical Repair of Tetralogy of Fallot

Abstract: Surgical correction of tetralogy of Fallot is still one of the most frequently performed intervention in pediatric cardiac surgery, and in many cases, it is far from being a complete and definitive correction. It is rather an excellent palliation that solves the problem of cyanosis, but predisposes the patients to medical and surgical complications during followup. The decision-making process regarding the treatment of late sequel is among the most discussed topics in adult congenital cardiology. In post-opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Routine congenital echocardiographic assessment of patients with repaired tetralogy of Fallot often focuses primarily on the right heart and ventricular function with little attention paid to the left atrium. 12,13 Qualitative assessment of left atrial enlargement may be flawed in this population as these estimates are often influenced by relative size to other heart structures. Patients with repaired tetralogy of Fallot frequently have a dilated right atrium as well as a dilated aortic root.…”
Section: Discussionmentioning
confidence: 99%
“…Routine congenital echocardiographic assessment of patients with repaired tetralogy of Fallot often focuses primarily on the right heart and ventricular function with little attention paid to the left atrium. 12,13 Qualitative assessment of left atrial enlargement may be flawed in this population as these estimates are often influenced by relative size to other heart structures. Patients with repaired tetralogy of Fallot frequently have a dilated right atrium as well as a dilated aortic root.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, tetralogy of Fallot (ToF) is the most common cyanotic congenital heart defect (Downing and Kim, 2015). While aspects of the physiology are now well appreciated by the congenital cardiac surgery community (Carminati et al, 2015), underlying mechanisms specific to the development of the disease require further elucidation. MiR research remains rather descriptive and only very few studies have tackled the genomic analysis of such CHD.…”
Section: Surgical Repair Of Congenital Heart Diseasementioning
confidence: 99%
“…There are multiple studies of PR evaluation in patients after surgical correction of conotruncal defects; [56][57][58][59][60][61][62][63] however, they were done mostly in adults, [61][62][63] or mixed population of adults and children. 64 Few studies focused on the pediatric age group.…”
Section: Pulmonary Regurgitationmentioning
confidence: 99%
“…63 echocardiography-derived right ventricular volumes have superior correlation with MRI measurements. 56 It is also important to evaluate LV function, which may be influenced by right ventricular dilation and dysfunction. 57 Speckle tracking echocardiography in patients after tetralogy of Fallot repair showed that not only the RV free wall longitudinal strain and strain rate were decreased, but also the LV longitudinal strain.…”
Section: Various Semiquantitative and Quantitative Indices For Pr Havmentioning
confidence: 99%